Liquefaction Potential Assessment for the City of Mamuju Sulawesi by using N-SPT based methods - Ardy Arsyad; Andi Asti Nur Amaliyah; Sopian Paerong; Abdul Rahman Djamaluddin (Himpunan Ahli Teknik Tanah Indonesia, 2022)
Mamuju is the capital city of West Sulawesi Province which has experienced severe damages along its infrastructures due to Majene Earthquake Mw. 6.2 on January 15th 2021. On that event, liquefaction phenomenon has been found on several places, triggering foundation settlements of buildings. Unfortunately, information on Mamuju’s earthquake hazard is still inadequate, while earthquake hazard assessment is urgently needed. Therefore, this study aims to assess liquefaction potential for the city of Mamuju. Serial geotechnical investigations were undertaken through a number of boreholes and N-SPT measurements. For liquefaction assessment, methods of estimating CRRM=7.5 were used including NCEER (1996), Vancouver Task Force (2007), Chinese Code, Japanese Highway Bridge Code, Shibata (1981), Boulanger & Idriss (2014), Cetin et al. (2004), Seed et al. (1983), Tokimatsu & Yoshimi (1983), and Kokusho et al. (1983), while estimation of CSR, the Simplified method (Seed, 1974) was employed. The results show that the coastal areas in the city has a high level of susceptibility to liquefaction. The liquefaction thickness of the ground would be 8 m deep for a 0.367g seismic acceleration (200 years return period earthquake), and 10 – 16 m for 0.414g seismic acceleration (deterministic Mw 7.0 of Fault Mamuju). Ground settlement induced by liquefaction was computed based on Ishihara & Yoshimi (1992) method. It was found that the ground settlement could be 18 – 50 cm, and 31 – 71 cm for each assumed seismic acceleration. The validity of the method used in this study was examined through the comparation of predictive liquefaction thickness and ground settlement based on the empiric methods with the measured ones in the field.